Study guides

☆☆

Q: How would you factor -6x squared minus 11x minus 4?

Write your answer...

Submit

Still have questions?

Related questions

(2x - 1)(5x + 8)

(x - 1)(2x - 9)

x^3 - 121x

Factor out -2: -2(x squared +11x-20). This is fully factored.

No answer in integers, nor outside the realm of imaginary numbers. Typo?

3x2 - 11x - 4 = (x-4)(3 x + 1)

That doesn't factor neatly. Applying the quadratic formula, we find two real solutions: (11 plkus or minus the square root of 14521) divided by 20. x = 6.575155599650519 x = -5.475155599650519

You have to experiment with different factors of 2, and different factors of 15. In this case, 2x2 - 11x + 15 = (2x - 5) (x - 3)

21

x = -28 / -11^2

I assume you mean...,X2 + 11X + 10(X + 1)(X + 10)==============factored

(11x - 2)(3x - 5)

I'm not sure this was notated correctly. As written, this is -11x plus or minus 18, which doesn't factor.

x^3 - 121x

x2 - 11x + 24 = (x - 3)(x - 8)

Assuming the question is written as: x2+11x-12 This would factor to: (x+12)(x-1)

There's a factor pair of 30 that adds up to 11. (x + 5)(x + 6)

3x2 - 11x - 4 = 0(3x + 1)(x - 4)x = -1/3 and 4

They are like terms and can be added together as 11x squared

x2 + 9x - 22 = x2 + (11 - 2)x + (11 x -2) = x2 + 11x -2x + (11 x -2) = (x + 11)(x - 2)

This is the equation we want to factorize: x2 - 11x + 18 And there are two answers (the numbers are the same, but +/- signs are inverted): 1. (x - 2)(x - 9) = x2 - 9x - 2x -(-18) = x2 - 11x + 18 2. (-x + 2)(-x +9) = x2 -9x -2x + 18 = x2 - 11x + 18

2x2 + 11x + 12 = 2x2 + 3x + 8x + 12 = x*(2x + 3) + 4*(2x + 3) = (2x + 3)*(x + 4)

It doesn't factor evenly if it were x**2-11x+10: x**2-11x+10 = (x-1)(x-10)

-x-6-(-11x) + (-1) Remove the brackets: -x-6+11x-1 Collect and simplify like terms: 10x-7 A - - is equal to a +

The "difference of squares" has a formula. (11x + 1)(11x - 1)